2003
DOI: 10.2308/accr.2003.78.1.275
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Information Complexity on Analysts' Use of That Information

Abstract: In this study I investigate the relation between information complexity and financial analysts' use of that information. I rank by complexity six tax-law changes enacted by the Tax Reform Act of 1986, and then examine analysts' explicit forecasts of effective tax rates around those changes. I show that analysts' revisions of their forecasts of effective tax rates appear to impound the effects of the less complex tax-law changes but not the more complex changes. Furthermore, as expected, if analysts assimilate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
162
3
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 314 publications
(177 citation statements)
references
References 31 publications
9
162
3
3
Order By: Relevance
“…As complexity increased, charismatic leaders seemed to prefer the pragmatic situation to either the ideological or charismatic situation. This finding is consistent with Mumford (2006), Kukalis (1991), andPlumlee (2003) who suggested that vision formation may prove difficult in ambiguous conditions. At first glance, this pattern is somewhat contradictory with the findings of Bedell-Avers et al (in press) that seemed to suggest charismatic leaders preferred less-structured conditions.…”
Section: General Findingssupporting
confidence: 82%
See 2 more Smart Citations
“…As complexity increased, charismatic leaders seemed to prefer the pragmatic situation to either the ideological or charismatic situation. This finding is consistent with Mumford (2006), Kukalis (1991), andPlumlee (2003) who suggested that vision formation may prove difficult in ambiguous conditions. At first glance, this pattern is somewhat contradictory with the findings of Bedell-Avers et al (in press) that seemed to suggest charismatic leaders preferred less-structured conditions.…”
Section: General Findingssupporting
confidence: 82%
“…As noted earlier, it may be difficult for a charismatic leader to form a future-oriented vision in highly complex conditions (Kukalis, 1991;Plumlee, 2003). In these highly complex conditions, however, charismatic leaders may be adequate problem-solvers if, indeed, asked to be (i.e., placed into a pragmatic situation).…”
Section: Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…First, previous research on accounting complexity has focused on studying the relationship between different measures of complexity and firm, manager, or user performance (e.g., Plumlee 2003;Bushman et al 2004;Li 2008;Miller 2010;Lehavy et al 2011;Peterson 2012;Filzen and Peterson 2015). Such studies generally measure complexity using quantitative proxies, which are presented as objective characteristics of complexity.…”
mentioning
confidence: 99%
“…Prior research focuses on various aspects of complexity in accounting through studies of organizational complexity (Bushman, Chen, Engle, and Smith 2004), financial reporting complexity (Li 2008;Miller 2010;Hobson 2011;Lehavy, Li, and Merkley 2011;Filzen and Peterson 2015), and information complexity (Plumlee 2003; 1 We refer to the accounting profession broadly as encompassing both accounting firms and professional accounting associations. We use the term accounting firms to refer to all firms in the accounting profession.…”
mentioning
confidence: 99%